A new Lagria Fabricius, 1775 from Xizang, China, with a checklist of Lagriini in Mêdog County (Coleoptera: Tenebrionidae: Lagriinae) - Zhou, Yong; Chen, Bin (Zootaxa, 2026)
Lagria (Lagria) cona sp. nov. is described from Cona City, Xizang, China. Key diagnostic characters include the bicolour elytra, meso- and metatibiae finely serrate in distal half, and the shape of the aedeagus. A checklist of Lagriini from Mêdog County is also presented.